A Case of Psychogenic Belching - Sharma, P; Sharma, P P; Chaudhary, D P; Bastola, P (Journal of Psychiatrists’ Association of Nepal, 2015)
Belching is the act of expelling air from the stomach through the mouth. It usually occurs when the stomach distends (expands) due to too much swallowed air, with the belching releasing the air to reduce the distention. We report here a case of psychogenic belching who was referred to psychiatry department after 3 months of her symptoms who responded to treatment quite effectively. J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 48-49 DOI: http://dx.doi.org/10.3126/jpan.v3i2.12395